Salmonella Enteritidis survival in different temperatures and nutrient solution pH levels in hydroponically grown lettuce - Xylia, Panayiota; Chrysargyris, Antonios; Botsaris, George; Skandamis, Panagiotis; Tzortzakis, Nikos G. (My University, 2022)
Due to climate change, with contaminated and less fertile soils, and intense weather phenomena, a turn towards hydroponic vegetable production has been made. Hydroponic cultivation of vegetables is considered to be a clean, safe and environmentally friendly growing technique; however, incidence of microbial contamination i.e. foodborne pathogens, might occur, endangering human health. The aim of this study was to investigate the effects of different plant growth stages, pH (values 5, 6, 7, 8) and bacterial inoculum levels (3 and 6 log cfu/mL) on hydroponically cultivated lettuce spiked with Salmonella Enteritidis. The results revealed that the pH and inoculum levels affected the internalization and survival of the pathogen in the hydroponic environment and plant tissue. Younger plants were found to be more susceptible to pathogen internalization compared to older ones. Under the current growing conditions (hydroponics, pH and inoculum levels), no leaf internalization was observed at all lettuce growth stages, despite the bacterium presence in the hydroponic solution. Noticeably, bacteria load at the nutrient solution was lower in low pH levels. These results showed that bacterium presence initiates plant response as indicated by the increased phenols, antioxidants and damage index markers (H2O2, MDA) in order for the plant to resist contamination by the invader. Nutrient solution management can result in Taylor-made recipes for plant growth and possible controlling the survival and growth of S. Enteritidis by pH levels.
Keywords: Internalization; Plant stress indicators; Foodborne pathogens; Hydroponics; Lettuce